Key internal factors leading to the variability in CO2 fixation efficiency of different sulfur-oxidizing bacteria during autotrophic cultivation. (1st October 2020) - Wang, Ya-nan; Kai, Yan; Wang, Lei; Tsang, Yiu Fai; Fu, Xiaohua; Hu, Jiajun; Xie, Yanjun
Abstract: Variability in the apparent CO2 fixation yield of four aerobic sulfur-oxidizing bacteria ( Halothiobacillus neapolitanus DSM 15147, Thiobacillus thioparus DSM 505, Thiomonas intermedia DSM 18155, and Starkeya novella DSM 506) in autotrophic culturing was studied, and mutual effects of key intrinsic factors on CO2 fixation were explored. DSM 15147 and DSM 505 exhibited much higher CO2 fixation yields than DSM 18155 and DSM 506. The differences in CO2 fixation yield were determined not only by cbb gene transcription, but also by cell synthesis rate, which was determined by rRNA gene copy number; the rRNA gene copy number had a more significant effect than cbb gene transcription on the apparent CO2 fixation yield. Moreover, accumulation of EDOC was observed in all four strains during chemoautotrophic cultivation, and the proportion of EDOC accounting for total fixed organic carbon (TOC; EDOC/TOC ratio) was much higher in DSM 18155 and DSM 506 than in DSM 15147 and DSM 505. The accumulation of EDOC led to a significant decrease in the cbb gene transcription efficiency during cultivation, and a further feedback inhibitory effect on CO2 fixation. Highlights: The CO2 fixation yield differed greatly in the four sulfur-oxidizing bacteria. Both cbb gene transcription efficiency and rRNA gene copy number affect CO2 fixation. The rRNA gene copy number plays a more significant role in CO2 fixation efficiency.